The effect of internet use on depressive symptoms in middle-aged and older adults with functional disability: the mediating role of social isolation - Wu, Man; Li, Chaoyang; Zhao, Xueyang; Hu, Ting; Zeng, Lijuan; Yu, Yiqing; Yang, Fen; Han, Yangyang (Frontiers in Public Health, 2023)
Objective The popularization of the internet provides the possibility to improve the depressive symptoms (DS) and social isolation of middle-aged and older adults with functional disability. There was a significant correlation between internet use and DS in middle-aged and older adults with functional disability, but the relationship between internet use, social isolation, and DS remains to be confirmed. Methods Data were obtained from 7,955 middle-aged and older adults aged 45 years and older from the 2018 China Health and Retirement Longitudinal Study (CHARLS). Multiple linear regression models were used to analyze the association between internet use and DS, and the Sobel test was used to explore mediating models. Results Results showed that internet use was negatively associated with DS among Chinese middle-aged and older adults. Among them, social needs (B = −0.770, p = 0.041), and information reception (B = −1.067, p = 0.007) were significantly related to DS in middle-aged and older adults. Only information reception (B = −3.161, p = 0.031) was significantly related to DS among middle-aged and older adults with functional disability. Social isolation partially mediated the association between internet use and DS in middle-aged and older adults without functional disability, whereas it was fully mediated in middle-aged and older adults with functional disability. Conclusion This study indicates that when formulating health policies to promote the mental health of Chinese middle-aged and older adults, the use of the internet should not be overlooked.